The Theory, Practice, and Interpretation of Customary International Law - Merkouris, Panos; Kammerhofer, Jörg; Arajärvi, Noora (Social Sciences, 2022)
This volume discusses the theory, practice, and interpretation of customary international law, as well as new developments and future research trajectories. Combining discussions of familiar concepts with new ideas, it is useful for researchers, scholars, and practitioners of international law. Available Open Access on Cambridge Core.